Urban wet weather pollution in combined sewer networks – Characteristics and origins - Gromaire-Mertz, M.C. (2nd World Forum on Water, 2000)
This research aimed to fit out an experimental urban catchment area (Le Marais catchment in Paris), provided with a combined sewer network and situated downtown, so as to obtain a description of the pollution of urban wet weather flows at different levels of the urban water cycle. This approach allowed: A detailed characterisation of the Pollution of waste water, of urban runoff from roofs, streets and yards, and, of combined flow at the catchment outlet. The parameters. we focused on were: event mean concentrations of SS, VSS, COD, BOD5, heavy metals (Cd, Cu, Pb, Zn) and hydrocarbons, distribution of the pollution between dissolved and particulate fractions; particle, characteristics. pollution loads on particles, settling velocities. distribution of the Pollution load during the rain event. An evaluation of the contribution of the three sources of pollution, which are urban runoff, waste water and to the pollution loads measured during a rain event at the outlet of the combined sewer. A study of the evolution of wet weather flow pollution between the entry and the outlet of the combined sewer. The results obtained underline the importance of combined sewers as physical and chemical reactors. The erosion of combined sewer sediments appeared to be the main source of particles and organic matter in wet weather flows, whereas heavy metal loads mainly originated from roof runoff, due to the corrosion of metallic roofs.